2022
DOI: 10.21601/aquademia/11828
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Best Practices in an Air Quality Student Science Project in Ethiopia

Abstract: A science project as part of a student's curriculum, which we call student science, might be the answer to two problems for a low-income country like Ethiopia: conventional science can be expensive and many students lack training in practical skills. Earlier studies have been conducted with respect to lay people (citizens or students) conducting (parts of) research (e.g. citizen science), but rarely in the context of a public university in a lowincome country. A student science project at Arba Minch University… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Data was collected with the student science method: letting students conduct research as part of their curriculum (Dingemanse & Dingemanse-de Wit, 2022). As part of a course, students in groups of 5-6 studied traffic air pollution.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data was collected with the student science method: letting students conduct research as part of their curriculum (Dingemanse & Dingemanse-de Wit, 2022). As part of a course, students in groups of 5-6 studied traffic air pollution.…”
Section: Data Collectionmentioning
confidence: 99%
“…However, a lack of resources has resulted in low research undertaking. This can be partially remedied with low cost sensors (Dingemanse, 2022a;Isaxon et al, 2019) and student science (Dingemanse & Dingemanse-de Wit, 2022). This study has applied both methods.…”
Section: Introductionmentioning
confidence: 99%
“…This falls under the umbrella of Citizen Science: science carried out at least in part by lay people or by a broader community than professional researchers (Kimura & Kinchy, 2016). For the topic of air quality in higher education specifically, a particularly promising approach is Student Science: to let students conduct science, as part of the students' curriculum (Dingemanse & Dingemanse-de Wit, 2022). This combines the benefits of crowdsourcing associated with Citizen Science with the additional educational value offered by participatory research (Zoellick et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Students of Arba Minch University have conducted measurements of PM 2.5 , CO, and CO 2 in a variety of self-selected air quality circumstances in their environment. This case of Student Science has been subject to a study in which it is found that Student Science can serve both scientific and educational needs typical for a university in Ethiopia (Dingemanse & Dingemanse-de Wit, 2022). The current study focuses on that scientific side and makes two main contributions.…”
Section: Introductionmentioning
confidence: 99%